1981
DOI: 10.1107/s0567739481000107
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-induced defects in β''-alumina examined by 1 MV high-resolution electron microscopy

Abstract: The defect blocks formed in fl"-alumina by electron irradiation are examined by 1 MV high-resolution electron microscopy. In order to explain the fact that two distinctly different types of defect images appear even in a single 1 MV micrograph, a new structural model is constructed in place of the two models so far Breported. In the model proposed, two spinel-like blocks on either side of the eliminated conduction plane are those expected from the spinel structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…(b) Crystal defects Another possible cause of local variations in crystal tilt is the disappearance of conduction planes under the influence of the electron beam. This process has been reported in sodium /3"-and p""-alumina (Matsui & Horiuchi, 1981;Matsui, 1981), and Figs. 6(a-c) show a similar event taking place in a sodium p"-alumina crystal observed at 200 kV, using the JEOL 200CX at Oxford University.…”
Section: R E S U L T S a N D Discussion S (A) Perfect Crystalsupporting
confidence: 72%
See 2 more Smart Citations
“…(b) Crystal defects Another possible cause of local variations in crystal tilt is the disappearance of conduction planes under the influence of the electron beam. This process has been reported in sodium /3"-and p""-alumina (Matsui & Horiuchi, 1981;Matsui, 1981), and Figs. 6(a-c) show a similar event taking place in a sodium p"-alumina crystal observed at 200 kV, using the JEOL 200CX at Oxford University.…”
Section: R E S U L T S a N D Discussion S (A) Perfect Crystalsupporting
confidence: 72%
“…A previous study of this layer in p"-alumina had indicated that in the edge-sharing tetrahedra produced by collapse and shear of the crystal after the loss of a conduction plane, 50",, of the aluminium ions in the upper tetrahedral site (i.e. that tetrahedron whose apex is below its horizontal face) move into adjacent octahedral sites, whilst 30",, of the aluminium ions in the lower tetrahedral site moved into octahedral sites (Matsui & Horiuchi, 1981). Figure 9 shows some of our results for p"-alumina, p"'-alumina and tilted p"'-alumina.…”
Section: (C) Defect Simulationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Na-β″-alumina has been widely investigated as a solid electrolyte for sodium–sulfur secondary batteries because of its high ionic conductivity, high density, and excellent stability against sodium metal [ 11 , 12 , 13 ]. The high mobility of Na + ions in the conduction plane of Na-β″-alumina stems from the large number of possible Na + sites between its spinel blocks [ 14 , 15 , 16 ]. With the chemical and structural analysis, the structure of Na β″-alumina was revealed, where Na ions are loosely linked between defective alumina spinels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, numerous studies have analyzed the atomic structure of Na-β″-alumina. In particular, such structural changes in Na-β″-alumina have been investigated using transmission electron microscopy (TEM) with electron beam irradiation because this accelerated beam can easily activate the Na ions on the conduction planes in β″-alumina [ 15 , 19 , 20 , 21 , 22 ]. For example, Bovin [ 19 ] carefully irradiated Na-β″-alumina with an electron beam and observed the growth of the spinel defect blocks via the conduction of Na + ions caused by the electron beam.…”
Section: Introductionmentioning
confidence: 99%